Evaluating Taxi Passenger Satisfaction Using IPA and CSI: Implications for Competitive Strategy in Indonesia - Athoillah, Ahmad Saifi (JBS Nexus, 2025)
In the last decade, the taxi industry in Indonesia has undergone significant changes with the arrival of app-based taxis such as Uber, Grab, and Go-Car (2014-2024). Changes in technology and information have driven a shift in people’s lifestyles, making online taxi services more desirable due to cheaper fares, efficient services, and ease of access. The purpose of this research is to analyze the level of satisfaction of conventional taxi passengers with online taxis in Indonesia. The number of respondents in this study amounted to 250 taxi passengers across Jakarta, Bogor, Depok, Tangerang, and Bekasi City areas (Indonesia). The sampling method used was convenience sampling, and the questionnaire survey was conducted by benchmarking five large taxi companies in Indonesia, namely PT ABC (company initials), PT Blue Bird Tbk, PT Uber Technology Indonesia, PT GrabBike Indonesia, and PT Gojek Indonesia. The variables in this study were tangible, reliability, assurance, responsiveness, empathy, product quality, and perceived value. The results showed that the IPA analysis variable attributes, placed PT ABC taxis in quadrants I, II, and III. While the CSI analysis found that the online taxi passenger satisfaction index is higher than the conventional taxi.